Cosmological Readings of Contemporary Australian Literature: Unsettling the Anthropocene - Bartha-Mitchell, Kathrin (Routledge Environmental Literature, Culture and Media, 2024)
This book presents an innovative and imaginative reading of contemporary Australian literature in the context of unprecedented ecological crisis. The Australian continent has seen significant, rapid changes to its cultures and land-use from the impact of British colonial rule, yet there is a rich history of Indigenous land-ethics and cosmological thought. By using the age-old idea of ‘cosmos’—the order of the world—to foreground ideas of a good order and chaos, reciprocity and more-than-human agency, this book interrogates the Anthropocene in Australia, focusing on notions of colonisation, farming, mining, bioethics, technology, environmental justice and sovereignty. It offers ‘cosmological readings’ of a diverse range of authors—Indigenous and non-Indigenous—as a challenge to the Anthropocene’s decline-narrative. As a result, it reactivates ‘cosmos’ as an ethical vision and a transculturally important counter-concept to the Anthropocene. Kathrin Bartha-Mitchell argues that the arts can help us envision radical cosmologies of being in and with the planet, and to address the very real social and environmental problems of our era. This book will be of particular interest to scholars and students of Ecocriticism, Environmental Humanities, and postcolonial, transcultural and Indigenous studies, with a primary focus on Australian, New Zealand, Oceanic and Pacific area studies.